Effect of Coordination on Employee Work Effectiveness in Nutrition and Pharmacy Installation - SRI - LULUK; lusi Afriyani (STIKES Bhakti Husada Mulia Madiun, 2020)
ABSTRACTIn a job, coordination is needed, because with good coordination the effectiveness of the work increases. The purpose of this study was to analyze the effect of coordination on the effectiveness of employee work in the Field of Support of the Regional General Hospital Dr. Sayidiman Magetan. The design of this study is analytical with a cross sectional approach. The total sample of 44 employees. The sampling technique in this study uses a nonprobability technique that is total sampling. The results showed that employees who had good coordination were 26 respondents (59.1%), who had less coordination of 18 respondents (40.9%), there were 31 respondents (70.5%) who worked effectively and 13 respondents (29.5 %) who work less effectively. By using the chi-square analysis shows the results, the value of ρ = 0,000 a = 0.05. The contingency coefficient value is 0.643. Contingency value of 0.643 is included in the strong category because it is in the range of 0.60 - 0.799. Staff coordination of 59.1% is good. The work effectiveness of 70.5% employees is effective. There is a coordinating effect on the effectiveness of the work of the Nutrition and Pharmacy Installation. All employees should work according to the SOP so that coordination and work effectiveness increases.